Transurethral use of nephroscope in the management of bladder stone - Sigdel, Ghanshyam S; Agarwal, A; Laminchhane, N; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2014)
Objective: Endoscopic management of bladder stone is a well established procedure. The objective of this study was to evaluate the usefulness of transurethral use of nephroscope in the management of bladder stones. Materials and methods: We retrospectively analyzed the medical records of patients who had undergone treatment of bladder stones through transurethral use of nephroscope in our hospital. Various demographic, stone related, intraoperative and postoperative parameters were studied. Results: The mean stone size was 18.1± 6.8 millimetres. Mean operative time and duration of hospital stay were 42.2 minutes and 2.4 days respectively. Intraoperative and postoperative complications occurred in 8 and 16 percent respectively, which were minor and managed without further interventions. Stone free rate was 100 percent. Conclusion: Bladder stones in adults can be effectively managed with the transurethral use of nephroscope without significant complications. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 14-18 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9668